Growing season and productivity of naked oats - N. V. Krotova; G. A. Batalova; Ren Changzhong; G. P. Zhuravleva (Аграрная наука Евро-Северо-Востока, 2020)
A well-studied source material is required for breeding problems to be successfully solved. Evaluation of samples in varying climatic conditions enables to identify highly productive sources. The results of assessment of 56 naked oat varieties of different ecological-geographical origin by duration of the growing season are presented. The studies were carried out in 2017 - 2019 on the sod-podzolic middle-clay soils of the Kirov region. Considerable differences between variety samples according to periods of ripening have been revealed. Classification of naked oat samples by duration of growing season for Volga-Vyatka region is proposed. The most numerous were the groups of middle season and middle-late samples – 41.1 and 35.7 %, respectively, late samples – 17.8 %. The set of early variety samples was very limited (5.4 %). The productivity of naked oat samples varied by years, variation level changed from insignificant to very high (V = 7.91...91.76 %). In the group of early varieties, coefficients of variation were 21.47...34.58 % with productivity of 165...330 g/m2. The evaluation of middle season samples showed mainly high and very high levels of variation in productivity. The exception was made by samples of Belarus k-3899 BYAS-154 (7.91 %) and 15094 MF9521-247 (16.83 %) from the USA with productivity of 139...161 and 182...244 g/m2, respectively. In middle-late and late variety samples, the coefficients of variation within the group were 21.44...68.36 %, and 26.25...68.75 %, respectively. Middle season samples with sustainable productivity are recommended for use in breeding practice, they are k-3897 BYAS-156, k-3898 BYAS-155 (Belarus), 15155 MF9016-31 (USA).